Developing of A Hierarchical Interface On-Line Data From Scada Systems To ERP Systems - Marwan Marwan (Jurnal Teknik Mesin Sinergi, 2008)
The purpose of this research is to address the problem of on-line data interconnectivity with development of a hierarchical interface which will be able to interchange on-line data from SCADA (Supervisory Control and Data Acquisition) systems to business process systems such as Enterprise Resource Planning (ERP) systems. Some preliminary investigation has been conducted such as the function of real-time data acquisition and monitoring systems of a water utility, and data filtering using a real-time compression algorithmic approach. In order to achieve the aim and objectives of this research, further modelling must be conducted such as refining the filtering algorithm, modelling systems and data hierarchy, identifying system related criteria and developing a hierarchical interface database.